Fuzzy Fixed Point Results For Φ Contractive Mapping with Applications - Humaira; Muhammad Sarwar; G. N. V. Kishore (Complexity)
In this paper, using rational type contractions, common fuzzy fixed point result for Φ contractive mappings involving control functions as coefficients of contractions in the setting of complex-valued metric space is established. The derived results generalizes some result in the existing literature. To show the validity of the derived results an appropriate example and applications are also discussed.